2020
DOI: 10.1111/pai.13213
|View full text |Cite
|
Sign up to set email alerts
|

The influence of species richness in primary school surroundings on children lung function and allergic disease development

Abstract: Background: Primary schools represent important environments for biodiversity exposure and thus may play a crucial role on early-life immunomodulation, protecting against allergic sensitization. The aim of this study was to understand how the exposure to different levels of species richness surrounding urban primary schools may influence the development of allergic diseases and asthma in children. Methods:A species richness index (SRI), evaluating habitat diversity in terms of amphibians, birds, reptiles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In fact, present study's results suggest that living proximate to more species at early‐life increases the risk of asthma and symptoms of asthma at the age of 7, as well as the prevalence of allergic disease in those living in neighbourhoods with a very high number of species, both at the ages of 4 and 7. This results are in agreement with those observed in a study where high levels of species richness surrounding primary schools were shown to be associated with a tendency for a higher prevalence of allergic diseases 46 . Interestingly, the association between SRI and eczema is not so evident in the present study, what could be explained by the differences in criteria for classifying the diseases, as well as the effect of vegetation.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, present study's results suggest that living proximate to more species at early‐life increases the risk of asthma and symptoms of asthma at the age of 7, as well as the prevalence of allergic disease in those living in neighbourhoods with a very high number of species, both at the ages of 4 and 7. This results are in agreement with those observed in a study where high levels of species richness surrounding primary schools were shown to be associated with a tendency for a higher prevalence of allergic diseases 46 . Interestingly, the association between SRI and eczema is not so evident in the present study, what could be explained by the differences in criteria for classifying the diseases, as well as the effect of vegetation.…”
Section: Discussionsupporting
confidence: 93%
“…Research has shown that nature can provide many benefits for public health. Exposure to nature, particularly to public green and blue spaces, is associated with numerous health benefits including better cardiovascular and respiratory health ( Lane Kevin, 2017 , Cavaleiro Rufo, 2020 ), improved immune ( Cavaleiro Rufo, 2020 ) and cognitive function ( de Keijzer, 2018 ), and lower risk of disease ( Twohig-Bennett and Jones, 2018 ) and mortality ( Gascon, 2016 ). Although most of the research has focused on the physical health benefits of nature exposure, there is growing evidence showing that both physical and visual contact with nature is associated with better mental health outcomes ( Wendelboe-Nelson, 2019 ) such as lower levels of stress, anxiety ( Triguero-Mas, 2017 ) and rumination ( Bratman, 2015 ), reduced prevalence of somatization symptoms ( Triguero-Mas, 2017 ), improved biomarkers of stress ( Ribeiro, 2019 ), and overall better psychological well-being ( Pearson and Craig, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In one example, adolescent atopy was found to have statistically significant negative associations with the abundance and species richness of particular native flowering plants, with these plants being ~25% more abundant around the homes of healthy individuals [ 35 ]. In a cross-sectional observational study, primary school children exposed to higher fungal and fauna diversity around their schools were less likely to develop allergic sensitisation and to have improved lung function, respectively [ 36 , 37 ]. Recent reviews have identified a lack of experimental and intervention studies with an explicit focus on testing the biodiversity hypothesis in the context of physical health [ 29 , 30 ].…”
Section: Recent Research Findingsmentioning
confidence: 99%